Use of macrofit indexes for evaluation environmental state of surface waters of Ukraine - Коробкова, Г. В. (Man and Environment. Issues of Neoecology, 1970)
Puporse. Approbation of the application of the method for assessment the ecological state of the rivers of the forest-steppe and steppe physiographic regions of Ukraine and justifying the possibility of using the aquatic macrophyte communities in the "Methodology for the Environmental Assessment of Surface Water Quality in the Corresponding Categories". Methods. Based on materials of the expeditionary surveys with the usage of MMOR Polish method the typing and  environmental assessment of Seversky Donets basin within the Kharkiv region are done. Results. The results of the application of the method for assessing the state of rivers with the help of macrophytes MOOR for the Seversky Donets River basin were carried out for the first time and showed significant consistency with earlier assessments of the ecological state of the Seversky Donets River on a complex of chemical and biological methods.The results of MIR indices varied within 23.0 - 37.9. The analyses of the obtained data indicates that "moderate" ecological status (Grade 3 – eutrophic status) was observed on the majority sites. "Good" status (Grade 2 – mesotrophic status) noted in 7 sites and  only 2 sites with "bad" status (Grade 5 – hippertrophic status). An spatial distribution ecological status by MIR of Seversky Donets River and its major tributaries within the Kharkiv region. The classification scheme for the use of the index MIR in the "Methodology environmental assessment of surface water quality for the respective categories" was done. Conclusions. The use of the MMOR method is advisable in the "Methodology for the Environmental Assessment of Surface Water Quality ...". The method allows to attract the macrophyte community to assess the ecological state of surface water bodies, which makes an ecological assessment of the quality of surface waters more thorough.